Peran Kepemimpinan Dalam Meningkatkan Kualitas Manajemen Bisnis Sekolah Di SMAN 2 Mandailing Natal - Muhammad Ardiansyah (Pusat Riset dan Inovasi Nasional, 2024)
The Service Learning approach has been adopted as a method to improve the quality of school business management at SMAN 2 Mandailing Natal. Through Service Learning, steps to identify community needs, project planning, implementation, evaluation and reflective learning have been carried out. With effective collaboration between school stakeholders and the local community, Service Learning projects succeed in providing real benefits to the surrounding community and strengthen students' skills and understanding of business management. As a result, SMAN 2 Mandailing Natal has been able to integrate business management principles into its school operations, including resource management, marketing and business strategy development. Thus, the Service Learning approach has brought positive changes in improving the quality of school business management, while producing a significant impact on local communities and student learning. This means that this article emphasizes that the role of leadership in encouraging Service Learning has been the key to success in developing quality and sustainable school business management.